Sustained complementary resistive switching capability deployed by structure-modulated electric field confinement of core-shell nanowires in a simple polymer composite - Kim, Min sung; Kim, Y.; Choi, Han Hyeong; Jeon, W.; Park, Jong Hyuk; Bang, J.; Lee, Sang-Soo (Elsevier BV, 2021)
In realizing high-density resistance random access memory (RRAM) crossbar arrays, the suppression of sneak current, a parasitic current flowing to unselected neighbor cells, has been critically required so far, due to the several repercussions such as unnecessary power consumption and misbehavior during the read operation. Recently, a complementary resistance switching (CRS) memory composed of two anti-serial RRAM elements has been proposed to overcome the sneak current problem. Herein, a novel CRS memory is proposed using core-shell nanowires instead of the multi-layered flat architecture of the typical CRS memory. The proposed CRS memory was prepared from a thin composite film comprising of the silver nanowire (AgNW) wrapped with SiO2 and a dielectric polymer matrix, and its CRS behaviors, as well as the governing mechanism, were extensively examined in terms of the structural parameters. It was demonstrated that the electric field confinement derived from the structural characteristic of the core-shell nanowires enabled facile ionization, fast migration of the generated Ag ions, and formation of Ag conductive filaments in highly localized regions, resulting in outstanding CRS performance including high Ron/Roff ratio and notably reproducible CRS behavior as well as low power consumption without any electronic failure during cyclic operation. ？ 2021 Elsevier Ltd